2008
DOI: 10.1177/0145482x0810200602
|View full text |Cite
|
Sign up to set email alerts
|

Educational Placement of Children who are Blind or have low Vision in Residential and Public Schools: A National Study of Parents’ Perspectives

Abstract: This study analyzed parents' perceived reasons for placing their children with visual impairments in residential or public schools. It found that children were more likely to be placed in residential schools for reasons related to their education and well-being and in public schools for reasons related to the parents' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Similarly, family preferences concerning placement may play a pivotal role in placement decisions for students with ASDs. In an analysis of why parents of children with visual impairments or blindness placed their child either in a public school or residential setting, Ajuwon and Oyinlade (2008) found that two variables had the greatest predictive value on this decision making: preferred classroom size (smaller size preferred when parents selected a residential setting) and attending school with a sibling (preferred when parents selected a public school). Similar factors related to family priorities may play an important role in ASDs placement decisions.…”
Section: Factors Effecting Placementmentioning
confidence: 99%
“…Similarly, family preferences concerning placement may play a pivotal role in placement decisions for students with ASDs. In an analysis of why parents of children with visual impairments or blindness placed their child either in a public school or residential setting, Ajuwon and Oyinlade (2008) found that two variables had the greatest predictive value on this decision making: preferred classroom size (smaller size preferred when parents selected a residential setting) and attending school with a sibling (preferred when parents selected a public school). Similar factors related to family priorities may play an important role in ASDs placement decisions.…”
Section: Factors Effecting Placementmentioning
confidence: 99%
“…Other factors may play a role, such as teacher training (Moreno, Aguilera, & Saldana, 2008) and availability of service providers (Dymond et al, 2007). It has been suggested that classroom size and ability to attend school with siblings influence parental decisions (Ajuwon & Oyinlade, 2008).…”
mentioning
confidence: 99%
“…A análise realizada por Celeste (2006) indicou que algumas dessas crianças recebem poucas respostas positivas pelas ofertas ou tentativas de se engajar em interações sociais com os colegas videntes. Isso pode resultar na diminuição do interesse por seus pares e torna as crianças cegas mais propensas ao isolamento (Ajuwon & Oyinlade, 2008).…”
Section: Introductionunclassified